Família de conversores CC/CC de alto ganho com célula diodo-capacitiva e célula multiplicadora de tensão aplicada a uma nanorrede CC residencial - Freitas, Antônio Alisson Alencar (2024)
This work presents a family of converters applied to multi-voltage direct current systems with a predominance of renewable energy sources for residential prosumers. The topologies presented in the work are non-isolated DC/DC converters the types of Boost, Cuk, and Zeta with the insertion of coupled inductors, diode-capacitive cell, and voltage multiplier cell. The use of direct current to internally power residences (nanogrids) is increasingly becoming a reality, due to the growth of consumers who also produce their own energy (prosumers) and due to the conversion losses inherent in a large part of electronic products when powered in alternating current. Due to the low cost of purchase and installation, photovoltaic panels have been leading the renewable energy sector applied to residential consumers; therefore, the study of DC/DC converters integrated with these panels is of high importance for the sector's growth. Thus, this work aims to develop DC/DC converters that have reduced weight and volume, that exhibit modularity, that do not use electrolytic capacitors, that have high static gain, and that have a non-pulsating output current, as these characteristics are of great importance regarding residential direct current systems. The topologies were analyzed qualitatively, examining their operation stages and their ideal waveforms, and quantitatively, studying their main equations in continuous conduction mode (CCM) and discontinuous conduction mode (DCM). To validate the proposed topologies, the high-gain Boost topology with coupled inductors, diode-capacitive cell, and voltage multiplier cell was implemented in the laboratory. The prototype has 200 W of power with an input voltage of 26 Vdc, an output of 380 Vdc, a switching frequency of 50 kHz, no electrolytic capacitor, and a current source characteristic at the input and output. Laboratory tests showed that the power switch operates under zero current transition (ZCT) condition at turn-on, and that the output diodes operate under zero current switching (ZCS) condition at turn-on and under zero voltage switching (ZVS) condition at turn-off. Thus, the converter showed an efficiency of 96.2% measured at 60 W and, under nominal power condition, of 94.35%, showing that the topologies presented in the work are robust and efficient to be used in residential systems powered by direct current.